Evaluation for permanence: a vision from the teaching experience - Villalpando Sifuentes, Celia Gabriela; Hernández Pérez, Claudio (IE Revista de Investigación Educativa de la REDIECH, 2017)
The evaluation for permanence is a compulsory exercise for in-service teachers who currently attract the attention of educational actors. As a process of subjective nature and significance for those involved, it needs to be addressed in a qualitative research, to know the implications of putting forward the Educational Reform through said valuation process in a present-day scenario. Considering this, it was imperative to review the contents of the Diario Oficial de la Federación, which is one of the documents that provides legal life to the aforementioned evaluation. Furthermore, theoretical referents were analyzed from specialists regarding the evaluation, as well as some authors to strengthen the foundation of the methodologic strategy. The research was positioned in the interpretative paradigm, specifically through studies in the case of teachers studying in a postgraduate institution in Ciudad Juarez; those of who have been subjected to the process of valuation tend to define their permanency in the Basic Education service. Amongst the findings we encounter the uncertainty experienced by the teachers in regards to their working conditions.